2022
DOI: 10.1007/s00520-022-07066-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the experiences of parents of children with cancer engaging in a mobile device-based resilience training programme: a qualitative study

Abstract: Purpose A mobile device-based resilience training programme has been found to improve psychological well-being in parents of children with cancer. However, the essential elements underlying the programme’s efficacy and the factors that affect parents’ advocacy of the online resilience training remain unknown. This study explored the lived experience of engaging in a mobile device-based resilience training programme in parents of children with cancer. Methods A descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…With regard to the web-based elements, the availability of different web-based learning tools has supported participants’ learning. This finding was consistent with prior research that evaluated web-based resilience programs [ 22 , 40 ]. Several key characteristics of web-based learning stood out.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…With regard to the web-based elements, the availability of different web-based learning tools has supported participants’ learning. This finding was consistent with prior research that evaluated web-based resilience programs [ 22 , 40 ]. Several key characteristics of web-based learning stood out.…”
Section: Discussionsupporting
confidence: 92%
“…Several key characteristics of web-based learning stood out. First, participants alluded to the importance of short attention-requiring materials such as videos, which was similarly reported in other studies [40,41]. Second, participants credited the availability of quizzes and homework that supplemented their learning.…”
Section: Principal Findingsmentioning
confidence: 61%
“…Resilience training is one intervention that has been used to help individuals cultivate the skills necessary to navigate the stress and overcome challenging situations 27 . Early research indicates that cultivating skills in resilience may help parents of childhood cancer patients better cope with the burden of disease 28 . Still, other studies showed that parents of children with cancer naturally demonstrate exceptional strength and resilience to the stressors of cancer, 29 suggesting that further research is needed to understand the determinants of the coping response in caregivers.…”
Section: Introductionmentioning
confidence: 99%